2018
DOI: 10.1080/10962247.2017.1394928
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of coupling a thermal/optical carbon analyzer to a quadrupole mass spectrometer for enhanced PM2.5 speciation

Abstract: Ammonium, nitrate, and sulfate can be quantified by the same thermal evolution analysis applied to organic and elemental carbon. This holds the potential to replace multiple parallel filter samples and separate laboratory analyses with a single filter and a single analysis to account for a large portion of the PM mass concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Speciation of organics in the atmospheric aerosol has usually accounted from about 20% or less of the total organic fraction. The simplified methods have allowed for "closure" of the aerosol mass balance with certain assumptions about the relation between organic matter and organic carbon (Turpin and Lim 2001;El-Zanan et al 2009;Chow et al 2018;Riggio 2018). However, the detailed mechanisms for formation of organic components vs. derivation from sources still require knowledge of organic speciation in the particles.…”
Section: Mass Concentration and Particle Compositionmentioning
confidence: 99%
“…Speciation of organics in the atmospheric aerosol has usually accounted from about 20% or less of the total organic fraction. The simplified methods have allowed for "closure" of the aerosol mass balance with certain assumptions about the relation between organic matter and organic carbon (Turpin and Lim 2001;El-Zanan et al 2009;Chow et al 2018;Riggio 2018). However, the detailed mechanisms for formation of organic components vs. derivation from sources still require knowledge of organic speciation in the particles.…”
Section: Mass Concentration and Particle Compositionmentioning
confidence: 99%
“…Reduction of the "sum of species" and OC abundances from fresh to aged profiles can be 292 offset by the formation of oxygenated organic compounds as the profiles age. Different 293 assumptions have been used to transform OC to organic mass (OM) to account for unmeasured H, 294 O, N, and S in organic compounds (Cao, 2018; Chow et al, 2015a; Riggio et al, 2018). As single 295 multipliers for OC cannot capture changes by oxidation in the OFR, OM is calculated by 296 subtracting mineral components (using the IMPROVE soil formula by Malm et al (1994)), major 297 ions (i.e., NH4 + , NO3 -, and SO4 = ), and EC from PM2.5 mass to account for unmeasured mass in 298 organic compounds (Chow et al, 2015a;Frank, 2006 The highest OM/OC ratios are found for Russian peat, ranging 1.6-1.7 for fresh profiles 309 and increasing to 2.1-2.2 for aged profiles, consistent with formation of low vapor pressure 310 oxygenated compounds in the OFR.…”
Section: Organic Mass (Om) and Om/oc Ratios 291mentioning
confidence: 99%